Meningkatkan Vokasional Membuat Boneka Pom-Pom Melalui Metode Latihan Terbimbing Bagi Anak Tunagrahita Ringan Kelas XI Di SLB Negeri 1 Padang - NurFatimah, Yulia (RC-INSTITUT, 2019)
This study discusses improving vocational making pom-pom dolls through guided training methods for mentally retarded children. This research uses classroom action research. The purpose of this study was to determine the process of improving vocational making pom-pom dolls through training methods for mentally retarded children and proving the guided training method can improve vocational making pom-pom dolls for mild retarded children. The study consisted of two cycles with three meetings each cycle, at the end of the learning evaluation was given. Research shows that guided training methods can improve vocational pom-pom dolls for mentally retarded children. The final results of research on students N, F and D in making pom-pom dolls have shown a good development in the application of manufacturing steps. So it can be concluded by using the guided training method in the learning process able to improve vocational making pom-pom dolls for children with mild mental disabilities.